(untitled) (Journal of Technology and Operations Management, 2020)
This paper will discuss the role of critical and creative thinking in preparing new generations to respond to the challenges threatening our societies today and in the future. We have been living in an ever interconnected and changing globalized world. Therefore, climate change, migration, international terrorism, financial meltdowns, poverty, injustices, and inequalities challenge and threaten the global community as a whole. If we want generations to come with new solutions and alternatives to solve these challenges, we must prepare them with critical thinking skills. It will suggest that the Qur’an and Sunnah of the Prophet were sources and driving forces of critical spirit in the classical Muslim legacy and kindled spirit of burning for learning. Therefore, this paper will attempt to define major concepts first and then delineate the significant features of critical and creative thinking in al-Ghazali’s exemplary life and teachings.